Load history effects on fatigue crack propagation: Its effect on the R-curve for threshold - X. Zhou; A. Hohenwarter; T. Leitner; H.P. Gänser; R. Pippan (Fracture and Structural Integrity)
The study deals with the effect of load history during threshold and fatigue crack propagation measurements in the near threshold regime. The compression pre cracking and the stepwise increasing load amplitude test was applied. The effects of pre-cracking as well as the effect of compression and tension overloads after the pre-cracking on the long crack threshold and on the R-curve of the threshold of stress intensity range are analysed.